Relief Pada Waruga Di Minahasa Dalam Perspektif Etnografis Dan Estetis = Relief on Waruga of Minahasa Its Aesthetics and Etnography - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Waruga is a grave that is made of sedimentary rock called tufa, or apela/ domato in its local language. This megalithic object of Minahasan ancestors is a unique and potential cultural inheritance which has invaluable historical values that have to be known by younger generation. This study analyzes the background of the existence of waruga tradition, form, function, the symbolic meaning of the motives of the relief, and its development. To reveal this problem is needs few approaches "to reread" the philosophy of the Minahasan people who lived several centuries ago, especially their concepts of meaning of life and death. Although there is no real documentation about the pioneers of waruga tradition, its presence was approximately after what was caled by the Westerners alifuru. It is a native religion which believes in supernatural energy that comes from both nature and the ancestors' spirits. The result of the study thows that, besides the aesthetical values, the visualization o the relief motives of waruga has a certain function and meaning that relates to the magic-religious belief. Changes of the motives from simple (ancient/ traditional) to the sophisticated form (complex/modern) were revealed when the society began to form ethnic groups with their formal leaders. The next development could be seen as the result of the coming of Westerners to Minahasa. When this phenomenon appeared, the existence of waruga and the ornaments were not simply as the veneration but they tend to be as the expression of respects. Although the way of life of Minahasan society was influenced by Western culture, especially in terms of Christianity, this study shows thAt had not changed the whole native culture of Minahasa at that time.